Patient safety begins with proper planning: a quantitative method to improve hospital design. Issue 5 (27th June 2010) - Birnbach, D J; Nevo, I; Scheinman, S R; Fitzpatrick, M; Shekhter, I; Lombard, J L
Abstract : Background: A quantitative methodology that enhances design of patient-safe healthcare facilities is presented. The prevailing paradigm of evaluating the design of healthcare facilities relies mainly on postconstruction criticism of design flaws; by then, design flaws may have already negatively affected patient safety. The methodology presented here utilises simulation-based testing in real-size replicas of proposed hospital designs. Other simulations to assess design solutions generated mainly qualitative data about user experience. To assess the methodology, we evaluated one patient safety variable in a proposed hospital patient room. Method: Fifty-two physicians who volunteered to participate were randomly assigned to examine a standardised patient in two hospital room settings using a replica of the proposed architectural plan; the two settings differed only by the placement of the alcohol-based hand-rub dispenser. The primary outcome was the hand hygiene compliance rate. Results: When the dispenser was in clear view of the physicians as they observed the patient, 53.8% sanitised their hands. When the dispenser was not in their field of view (as in the original architectural plan), 11.5% sanitised their hands (p=0.0011). Based on these results, the final architectural plans were adjusted accordingly. Conclusion: The methodology is an effective and relatively inexpensive means to quantitatively evaluate proposed solutions, which can then be implemented to build patient-safe healthcare facilities. It enables actual users to proactively identify patient safety hazards before construction begins.